Global-scale patterns and determinants of cropping frequency in irrigation dam command areas. (May 2018) - Rufin, Philippe; Levers, Christian; Baumann, Matthias; Jägermeyr, Jonas; Krueger, Tobias; Kuemmerle, Tobias; Hostert, Patrick
Highlights: Spatially explicit mapping of irrigation dam command areas on a global scale. Cropping frequency in irrigation dam command areas 16% above rainfed areas. Inefficient water transfer potentially constrains intensive cropping. Future emphasis on regional scale irrigation system governance is advised. Abstract: A growing human population and shifting consumption patterns increase the pressure on agricultural production systems. Reservoir-based irrigation has boosted agricultural production through higher cropping frequencies, whereas the magnitude of this effect varies significantly across the globe. Technological, biophysical and socio-economic constraints often limit cropping frequency in the command areas of irrigation dams, yet the relationships with these factors remain poorly understood at the global scale. Here, we first determined the size and location of 1288 command areas of irrigation dams commissioned since 1985. Within these areas, we studied cropping frequency during the period of 2001–2012 using a global time series of land cover information. We further investigated potential biophysical, socio-economic and technological constraints for intensive cropping using a Boosted Regression Trees modeling framework. Our results showed that the largest extent of reservoir-irrigated croplands are located in India (5.9 Mha), Indonesia (1.5 Mha), China (1.4 Mha), Vietnam (0.9 Mha), Turkey (0.7 Mha), Iran (0.7 Mha), and Thailand (0.6 Mha). Globally, cropping frequencies in irrigation dam command areas were on average 16% higher compared to rainfed control areas, yet pronounced differences in the strength and direction of this effect were apparent across world regions. Technological properties of dams and irrigation systems were amongst the most important variables for explaining global-scale variation in cropping frequency. Specifically, we observed low cropping frequencies in smaller command areas (<10, 000 ha) and under long distance water allocation (>20 km). The command areas of small reservoirs (storage capacity < 7.9 Mm³) showed similar cropping frequencies compared to large reservoirs, yet with increased tolerance toward biophysical constraints. Our findings thus support arguments for future emphasis on de-centralized water storage facilities in order to reduce water losses and to improve access to irrigation water and infrastructure, thereby contributing to better meeting future agricultural production targets.